2009
DOI: 10.1021/jm801512v
|View full text |Cite
|
Sign up to set email alerts
|

Octahydrophenanthrene-2,7-diol Analogues as Dissociated Glucocorticoid Receptor Agonists: Discovery and Lead Exploration

Abstract: As exemplified by the lead compound 2, octahydrophenanthrene-2,7-diol analogues exhibit the profile of a pathway-selective or "dissociated" agonist of the glucocorticoid receptor (GR), retaining the potent activity that glucocorticoids have for transrepression (as measured by inhibition of IL-1 induced MMP-13 expression) but showing an attenuated capacity for transactivation (as measured in an MMTV luciferase reporter assay). With the guidance of a homology model of the GR ligand binding domain, structural mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…A closer inspection of the bound alkyne is equally informative. The substantial elongation of the CC bond indicates a high degree of activation which is qualitatively in line with the massive deshielding observed by 13 C NMR. Interestingly, the CC bond in 5 (1.283(1) Å) is longer than that in 4 (1.264(4) Å) and the alkyne slightly more bent away from linearity (C3–C2–C1 144.75(8)° versus 145.3(3)°).…”
Section: Results and Discussionsupporting
confidence: 80%
“…A closer inspection of the bound alkyne is equally informative. The substantial elongation of the CC bond indicates a high degree of activation which is qualitatively in line with the massive deshielding observed by 13 C NMR. Interestingly, the CC bond in 5 (1.283(1) Å) is longer than that in 4 (1.264(4) Å) and the alkyne slightly more bent away from linearity (C3–C2–C1 144.75(8)° versus 145.3(3)°).…”
Section: Results and Discussionsupporting
confidence: 80%
“…10 In our first paper, we described the discovery of a novel series of DAGRs containing the octahydrophenanthrene-2,7-diol pharmacophore (1−5, Table 1). 5 These analogues functioned as agonists in in vitro assays of TR (inhibition of IL-1 induced IL-8 and MMP-13 expression) but possessed reduced capacity for TA in an assay measuring activation of a mouse mammary tumor virus (MMTV) reporter construct, as compared to DEX. In addition, we outlined our early optimization efforts on this series focusing on replacing the allyl (R 4 ) and particularly the propynyl (R 2 ) substituents with those more likely to be chemically stable and less likely to produce toxic metabolites.…”
Section: ■ Introductionsupporting
confidence: 92%
“…This has led to the discovery of a novel pharmacophore that demonstrated a spectrum of TR/TA activities that differed from those of classical GR agonists. 5 Arguably, compounds displaying such dissociated activities represent potential candidates to test for improved safety/efficacy profiles in human. In fact, a recent phase 2 clinical study with DAGR PF-04171327 has shown similar efficacy to 10 mg of PRED but with effects on bone formation and glucose markers at 5 mg of PRED.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Evidence of the clear interest in the field of non-steroidal dissociated GR ligands is provided by the considerable number of compounds reported (reviewed in [60]) that are able to bind GR with a more favorable profile as compared to standard classic GCs. These include Boehringer Ingelheim's BI 115 and Compound 36 [61], GSK's tetrahydronaphthaline-methylbenzoxazinones [62] and arylpyrazoles [63] or a 6,5-bicyclic core fused to a pyrazole ring (Merck) [64], Compound 15 (UCSF), Compound 25 (Merck), or the recently reported Compound 2 (Pfizer) [65]. Data on side effect parameters are still lacking for many of these compounds.…”
Section: Non-steroidal Gr Modulatorsmentioning
confidence: 99%